2014
DOI: 10.1136/bmj.g7267
|View full text |Cite
|
Sign up to set email alerts
|

Nintendo related injuries and other problems: review

Abstract: Most problems are mild and prevalence is low. The described injuries were related to the way the games are controlled, which varies according to the video game console.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 51 publications
0
19
0
2
Order By: Relevance
“…Activities with this type of games have the potential to generate health benefits, improving physical fitness/ability, besides getting children and adolescents involved in physical activities of moderate intensity [20]. Also, there is no evidence on adverse effects of exercising using video games in CF patients, although case studies have reported Wii-related injuries due to prolonged or overly aggressive play [21].…”
Section: Introductionmentioning
confidence: 98%
“…Activities with this type of games have the potential to generate health benefits, improving physical fitness/ability, besides getting children and adolescents involved in physical activities of moderate intensity [20]. Also, there is no evidence on adverse effects of exercising using video games in CF patients, although case studies have reported Wii-related injuries due to prolonged or overly aggressive play [21].…”
Section: Introductionmentioning
confidence: 98%
“…“Gamification” of therapy (or game-based therapy) in rehabilitation is a strategy that can potentially address motivation and compliance and has been shown to increase compliance [37]. However, gaming, if not performed properly can also lead to injury [38]. …”
Section: Introductionmentioning
confidence: 99%
“…Video game-related injuries have been widely observed since the advent of video games [33,34]. As the video game market shifted from exclusively controller-based games to include motion-tracking technologies, physical risks of gameplay increased, with the potential for more traumatic injuries to the entire body [33].…”
Section: Physical Safetymentioning
confidence: 99%